Utilization of the multi-criteria optimization for modeling the signal restoring process of differential transforms - Жуков, І. А.; Засядько, А. А. (Proceedings of National Aviation University (archive), 2021)
The use of differential Taylorian transforms for modeling the signal restoring process of differential transforms is regarded. The differential Taylorian model for the restoring problem is constructed. The numerical algorithm for solving the equations is given and its advantages are described. The system of bad condolence linear algebraic equations described, is solved by means of multicriteria optimization. The partial criteria are proposed; on the base of these criteria the vector of effectiveness that is a non-linear compromise schema is constructed. The obtained solution is optimal.